Contextualizing crime as an environmental stressor on mental health in urban communities - A scoping review - Qian He (Social Sciences and Humanities Open)
Crime is increasingly recognized as an environmental stressor contributing to mental health disparities in urban communities. While scholars in public health, criminology, and urban planning have explored this relationship, no scoping review has synthesized the existing evidence through the lens of neighborhood environments and the social determinants of health. This scoping review maps and analyzes peer-reviewed literature published between 2000 and 2020 to identify theoretical frameworks, methodological trends, and empirical findings on the relationship between crime, mental health, and the built and social environments. The findings highlight how urban inequities, environmental characteristics, and social ties intersect to shape psychological well-being. Drawing on feminist perspectives, social vulnerability theory, and research on systemic racism, this review offers critical insights for urban planners and policymakers. It concludes with recommendations for trauma-informed and equity-centered planning strategies to address the mental health impacts of crime in historically marginalized urban neighborhoods.